Cognitive-behavioural theories and adherence: Application and relevance in antiretroviral therapy - Adegoke O. Adefolalu (AOSIS, 2018)
Background: Adherence in chronic disease conditions is described as the extent to which a person's behaviour corresponds to the prescribed medical advice of the healthcare provider. This is not limited to medication intake only but also includes acts such as following instructions regarding dietary or fluid restrictions and taking medicines at the prescribed times and intervals. Although adherence to antiretroviral therapy (ART) is a predictor of good clinical outcome among HIV-infected persons on ART, it is a major challenge and strict adherence is not very common. This article aims to examine the application and relevance of some cognitive-behavioural theories in antiretroviral therapy adherence Methods: After doing a thorough literature review, contemporary theories of health behaviour at the individual and interpersonal levels referred to as cognitive-behavioural theories were explored. This review highlights some aspects of the cognitive perspective of health behaviour theories as a good theoretical framework that could be used for organising thoughts about adherence and other health behaviours among patients on lifelong treatment such as ART. Results: Key concepts of these theories stipulate that behaviour is mediated by cognition i.e. knowledge and attitude affect the person's action. In addition, cognitive-behavioural theories recognise knowledge alone as being insufficient to produce behavioural change; a person's perception, motivation, skills and social environment are all influential in the process of behavioural change. Conclusion: Prediction of medication adherence is complex, and health-related knowledge and beliefs alone are insufficient to achieve behaviour change, especially in chronic conditions such as HIV/AIDS. However, people can control or influence the events affecting their lives by integrating cognitive, social, and behavioural sub-skills related to beliefs of personal efficacy in performing these skills.